2022
DOI: 10.1097/aci.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of severe asthma exacerbations

Abstract: Purpose of reviewAsthma exacerbations are major factors in asthma morbidity and also have long-term consequences.Recent findingsAsthma is characterized by an accelerated and progressive loss of lung function. Recent evidence has pointed to the frequency of exacerbations as being a significant contributor to a loss of lung function in asthma.SummaryA consequence of asthma exacerbations is a greater loss of lung function. Airway inflammation is central to asthma severity and susceptibility for exacerbations. Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…[28][29][30] Increasing lung function loss is caused by asthma exacerbations and is further affected by the escalation of airway inflammation that occurs during an asthma exacerbation. 31,32 In this study, a BDR ≥20% and severe asthma exacerbations were identified as predictors of aOR=adjusted odds ratio; BDR=bronchodilator responsiveness; CI=confidence interval; cOR=crude odds ratio; FEF 25- recurrent asthma exacerbations. However, only BDR ≥20% was identified as an independent predictor of asthma exacerbation.…”
Section: Discussionmentioning
confidence: 79%
“…[28][29][30] Increasing lung function loss is caused by asthma exacerbations and is further affected by the escalation of airway inflammation that occurs during an asthma exacerbation. 31,32 In this study, a BDR ≥20% and severe asthma exacerbations were identified as predictors of aOR=adjusted odds ratio; BDR=bronchodilator responsiveness; CI=confidence interval; cOR=crude odds ratio; FEF 25- recurrent asthma exacerbations. However, only BDR ≥20% was identified as an independent predictor of asthma exacerbation.…”
Section: Discussionmentioning
confidence: 79%
“…SEA patients experience frequent exacerbations and often rely on high-dose OCS, which are strongly associated with major adverse events, in order to manage or prevent their occurrence [ 7 ]. Exacerbations are also associated with reduced pulmonary function and a significant increase in hospitalizations [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these differences in improvements with tezepelumab versus placebo are of lower magnitude than those observed in patients with T2-high asthma, and the 95% confidence intervals include zero, it is important to note that the observed trends of improvement for these outcomes do not rule out meaningful improvement for individual patients. Additionally, asthma exacerbations are discrete events that are specific to asthma pathophysiology and are considered a major factor in asthma morbidity ( 5 ). However, assessments of patient-reported symptoms and HRQoL are inherently more variable and less precise, and clinical trial assessments are complicated by large improvements from baseline among placebo recipients.…”
mentioning
confidence: 99%